2017
DOI: 10.1016/j.buildenv.2017.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Ceiling fan air speeds around desks and office partitions

Abstract: Ceiling fans may cool room occupants very efficiently, but the air speeds experienced in the occupied zone are inherently non-uniform. Designers should be aware of several generic flow patterns when positioning ceiling fans in a room. Key to these are the fan jet itself and lateral spreading near the floor. Adding workstation furniture redirects the jet's airflow laterally in a deeper spreading zone, making room air flows more complex but potentially increasing the cooling experienced by the occupants. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 15 publications
4
42
1
Order By: Relevance
“…al. [27] showed that when the fan jet impinges directly on furniture, it widens the higher air speed region beyond the fan diameter, however, the majority of the room still has lower air speeds. This difference between higher air speeds in one location than in others may be problematic where there are multiple occupants who cannot freely or easily move about the room, with some too cool and some too warm depending on where they happen to be located.…”
Section: Technical Barriers To Use Of Increased Air Movementmentioning
confidence: 99%
See 2 more Smart Citations
“…al. [27] showed that when the fan jet impinges directly on furniture, it widens the higher air speed region beyond the fan diameter, however, the majority of the room still has lower air speeds. This difference between higher air speeds in one location than in others may be problematic where there are multiple occupants who cannot freely or easily move about the room, with some too cool and some too warm depending on where they happen to be located.…”
Section: Technical Barriers To Use Of Increased Air Movementmentioning
confidence: 99%
“…We reviewed previous investigations on air speed distribution induced by a ceiling fan, focusing on the factors which affect that distribution. These factors include fan rotational speed [8,[30][31][32][33], blade shape and number [31,32,34,35], direction (upward or downward) [30,[36][37][38], mount distance [32,36], ceiling height [32], multiple fans [26,33], and furniture [26,27].…”
Section: Review Of Prior Studies Investigating Ceiling-fan Driven Airmentioning
confidence: 99%
See 1 more Smart Citation
“…First, detailed laboratory measurements of occupied zone air speeds, with and without furniture, have been taken under a single ceiling fan. The detailed measurements profiles are described [13].…”
Section: Ceiling Fan Evaluation Approachesmentioning
confidence: 99%
“…Simulations in this study are based on a previous experimental study of an office room conducted at the Center for the Built Environment (CBE) at University of California, Berkeley [13]. The room had geometries of 5.5 (X) × 5.5 (Z) × 2.5 (Y) m, as shown in Fig.…”
Section: Baseline Experimental Datamentioning
confidence: 99%